Princess Jellyfish. 05 - Higashimura, Akiko (Kodansha Comics, 2017)
Tsukimi Kurashita has a strange fascination with jellyfish. She's loved them from a young age and has carried that love with her to her new life in the big city of Tokyo. There, she resides in Amamizukan, a safe-haven for girl geeks who regularly gush over a range of things from trains to Japanese dolls. However, a chance meeting at a pet shop has Tsukimi crossing paths with one of the things that the residents of Amamizukan have been desperately trying to avoid--a fashionable socialite!